Family and household religion in ancient Israel and the Levant - Albertz, Rainer, 1943- (Eisenbrauns, 2012)
It details family religious beliefs as expressed in the almost 3,000 individual Hebrew personal names that have so far been recorded in epigraphic and biblical material. The Hebrew onomasticon is further compared with 1,400 Ammonite, Moabite, Aramean, and Phoenician names. These data encompass the vast majority of known Hebrew personal names and a substantial sample of the names from surrounding cultures. In this impressive compilation of evidence, the authors describe the variety of rites performed by families at home, at a neighborhood shrine, or at work. Burial rituals and the ritual care for the dead are examined. A comprehensive bibliography, extensive appendixes, and several helpful indexes round out the masterful textual material to form a one-volume compendium that no scholar of ancient Israelite religion and archaeology can afford not to own.